New Design of Aluminum 6061 Welding Joining Using Friction Stir Welding Method - Setiawan, Widia; Santoso, Nugroho; Surojo, Surojo (Journal of Mechanical Engineering Science and Technology (JMEST), 2020)
Parallel, lap, corner, and T joints are commonly used in fusion welding and solid welding. Other joints made are lap and butt joint. This study aims to evaluate a new design of fitting model single U and double U for friction stirr welding of Aluminum. Aluminum sheet 6061with a thickness of 10 mm, will be cut to a length of 150 mm and a width of 100 mm, then a locking groove will be made with an inner size of 5 mm and a length of 150 mm The flow is used to be paired in the FSW process. This experiment results show the high tensile strength that occurs in the double joint u, is 13.4 kN while the average is 12 kN. Single connection experiment u the highest tensile strength is 12.89 kN, while the average value is 10.37 kN. The hardness is higher in double u joints compared to single u joints.